2018
DOI: 10.1161/circulationaha.116.024332
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of the CREST Model for Very Early Prediction of Circulatory Etiology Death in Patients Without ST-Segment–Elevation Myocardial Infarction After Cardiac Arrest

Abstract: The CREST model stratified patients immediately after resuscitation according to risk of a circulatory-etiology death. The tool may allow for estimation of circulatory risk and improve the triage of survivors of cardiac arrest without ST-segment-elevation myocardial infarction at the point of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…The main issue is to identify the most suitable patients with post-resuscitation shock eligible for ECLS. Bascom and colleagues have proposed to use the “CREST score” (Table 1 ) for early identification of patients carrying the highest risk of circulatory-related death after CA, who could, therefore, be elective candidates for ECLS [ 82 ]. It has also been shown that in patients with post-resuscitation shock treated by ECLS, admission SOFA score < 14, initial shockable rhythm and international normalized ratio < 2.4 as well as initial arterial pH (odds ratio = 1.7 per 0.1 increase) and implantation of ECLS later than 24 h after ROSC were associated with survival and thus could be useful triage tools in such patients [ 83 , 84 ].…”
Section: Management Of Post-resuscitation Shockmentioning
confidence: 99%
“…The main issue is to identify the most suitable patients with post-resuscitation shock eligible for ECLS. Bascom and colleagues have proposed to use the “CREST score” (Table 1 ) for early identification of patients carrying the highest risk of circulatory-related death after CA, who could, therefore, be elective candidates for ECLS [ 82 ]. It has also been shown that in patients with post-resuscitation shock treated by ECLS, admission SOFA score < 14, initial shockable rhythm and international normalized ratio < 2.4 as well as initial arterial pH (odds ratio = 1.7 per 0.1 increase) and implantation of ECLS later than 24 h after ROSC were associated with survival and thus could be useful triage tools in such patients [ 83 , 84 ].…”
Section: Management Of Post-resuscitation Shockmentioning
confidence: 99%
“…Our findings also revealed a tendency for more severe CAD and larger infarcts sizes (reflected by higher troponin elevations) in non-survivors although it didn't reach statistical significance, pointing to the need of larger studies to prove its impact on survival LVEF is considered an echocardiographic measure of myocardial dysfunction but its prognostic significance in OHCA patients is controversial and robust data is missing. Some observational studies report an association between LV dysfunction and survival [27,28] while others [3,29,30], like ours, found that it doesn't impact outcomes. Interestingly, Jentzer et al, showed that diastolic dysfunction is associated with inhospital and long-term mortality, considering it a more important variable in predicting patient outcomes [31].…”
Section: Cardiac Findingsmentioning
confidence: 45%
“…The CREST model identified five variables in patients without ST elevation that could predict, with moderate accuracy, patients at higher risk of cardiac aetiology death. [143] Integration of these risk scores into prospective clinical trials may provide objective information to support decision making on arrival to the cardiac catheterisation laboratory.…”
Section: Management In the Cardiac Catheterisation Laboratorymentioning
confidence: 99%